Analisis Kepatuhan Syariah pada Perbankan Syariah Digital dalam Perspektif Literatur - Dino Baggio Listiyanto; Muhamad Solahudin; Pika Amalia; Elinda Nur Hasanah; Suci Aulia (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
This study aims to analyze the literature on sharia compliance in Islamic digital banking. It employs a qualitative approach using a literature review method, with data collected from books, academic journals, and regulations issued by the Financial Services Authority (OJK) and the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). The results show that digital transformation in Islamic banking provides significant benefits, including improved operational efficiency, wider service accessibility, and enhanced financial inclusion. However, the implementation of digital banking services must strictly adhere to sharia principles, such as the prohibition of riba, gharar, and maysir, while ensuring transparency and consumer protection. The study also highlights several challenges, including limited customer understanding of digital contracts, potential lack of system transparency, data security and privacy risks, and the shortage of qualified human resources in both sharia and technology fields. In addition, regulatory frameworks and supervisory mechanisms need to be more adaptive to rapid technological advancements. Strengthening sharia governance, improving human resource capacity through continuous training, and enhancing collaboration among regulators, fatwa institutions, and internal supervisory bodies are essential to support the sustainable development of Islamic digital banking.